Comparative evaluation of the effect of conventional and truss access cavities on remaining dentin thickness, canal transportation, and canal centering ability in mandibular molars using cone-beam computed tomography - Karkala Venkappa Kishan; Krushn Savaliya; Manan Shroff; Purnima Saklecha (Wolters Kluwer Medknow Publications, 2023)
Aim: To evaluate and compare the effect of conventional and truss access cavity preparations on remaining dentin thickness (RDT), canal transportation, and centering ability in mandibular molars using cone-beam computed tomography (CBCT). Methods: Ethical approval was obtained before the commencement of the study. Thirty extracted mandibular molars were selected, disinfected, and stored in normal saline. Preoperative CBCT scans were taken for all the samples and randomly divided into two groups. (n = 15). Group A; Conventional access preparation group; Group B; Truss access preparation group. Cleaning and shaping were performed with the mesiobuccal canal of all the samples. Postoperative CBCT scans were compared with preoperative CBCT scans to evaluate the RDT, canal transportation, and canal centering ability in mandibular molar with conventional and truss access cavity preparation. Results: Data obtained from CBCT were analyzed by independent sample t-test with the P < 0.05 and found that RDT was higher in Group A as compared to Group B at the 3 and 9 mm levels, whereas it was higher in Group B at 6 mm level in both the mesial and distal side, but it was statistically insignificant at 3, 6, and 9 mm level. Canal transportation was higher in Group B than in Group A, but it was statistically insignificant at 6 and 9 mm levels but statistically significant at 3 mm. Canal centering ability was higher in Group A than in Group B, but it was not statistically significant at 3, 6, and 9 mm levels. Conclusion: Regarding RDT and canal centering ability, there is no statistically significant difference at all levels. Both groups present a statistically significant difference at 3 mm from the apex when comparing canal transportation. This suggests that conventional access cavity preparation is better than truss access preparation to maintain original canal anatomy.